Answer:
4(2e - 3)(3e + 1)
Step-by-step explanation:
Given
24e² - 28e - 12 ← factor out 4 from each term
= 4(6e² - 7e - 3) ← factor the quadratic
Consider the factors of the product of the e² term and the constant term which sum to give the coefficient of the e- term.
product = 6 × - 3 = - 18 and sum = - 7
The factors are - 9 and + 2
Use these factors to split the e- term
6e² - 9e + 2e - 3 ( factor the first/second and third/fourth terms )
= 3e(2e - 3) + 1 (2e - 3) ← factor out (2e - 3) from each term
= (2e - 3)(3e + 1)
Then
24e² - 28e - 12 = 4(2e - 3)(3e + 1) ← in factored form
I think it might be expression one =14 i think and number 2 is obviously is 19 but you would put parenthesis around 5+4_2+6
I think i did this right its been a while since i did this
Answer:
a = 42 b = 21
Step-by-step explanation:
a is 42 since it ks vertically opposite 42
To solve for b
360 - (42×2)........to get the angle next to a
=276... Divde answer by 2. Bc there are two of the angles
276÷2 =138
138 + 2b =180
2b = 180 - 138
b = 42 ÷ 2
b = 21